Design, Synthesis and Biological Evaluation of Novel Inhibitors of InhA from Mycobacterium tuberculosis - Armstrong, Tom (2021)
Multi-drug resistant tuberculosis (MDR-TB) represents a growing problem for global healthcare systems. The World Health Organisation reported 1.3 million deaths from tuberculosis in 2019, making the disease a leading cause of global mortality. In addition to this, there is an increasing spread of drug-resistant tuberculosis infections, with 390,000 new cases of MDR-TB recorded in 2019, these are infections resistant to Rifampicin and Isoniazid. Isoniazid is a key anti-TB drug and an inhibitor of InhA, a crucial enzyme in the cell wall biosynthesis pathway and identical in Mycobacterium tuberculosis and Mycobacterium bovis. Isoniazid is a prodrug which requires activation by the enzyme KatG, this active species then forms an adduct with the NAD+ cofactor which then binds to InhA and prevents substrate recognition. Mutations in KatG prevent this activation and confer INH-resistance. ‘Direct inhibitors’ of InhA are attractive as they would circumvent the main clinically observed resistance mechanisms.